The lessons learned from emerging and “eternal” pollutants in groundwater: per- and polyfluoroalkyl substances - Giovanni Pietro Beretta (Acque Sotterranee)
The new substances resulting from anthropic production found in environmental matrices for some years have been defined as emerging pollutants. This is the case of PFAS in groundwater, first identified in the Regione Veneto over 10 years ago and later also in other areas of Italy, which could act as an emblematic example. The per- and poly-fluoroalkyl substances (PFAS) have been manufactured and used in a variety of industries around the globe since the 1940s, and they are still being used today. [...]